PERCEPTIONS OF JUSTICE BY VICTIMS OF SEXUAL VIOLENCE IN NIGERIA - Udonnah, Glory Boniface (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
The experience of being sexually violated is traumatic enough, but for many victims, approaching the criminal justice system in pursuit of justice for the violation of their right to dignity becomes a second trauma. While legal and institutional frameworks exist to punish offenders and provide protection for the victims, the realities of accessing justice with ease remain deeply flawed. The perception of justice by victims is not only shaped by outcomes but starts from their initial contact with the police, who are the gatekeepers of the criminal justice system. Furthermore, how societies respond to their disclosure is also essential. Understanding this perception is vital for a justice system that is fair and just. This article aims to explore how victims of sexual violence perceive justice within institutional and legal frameworks and whether the responses meet their needs and expectations. Using a doctrinal approach, a careful examination of various factors is needed to assess the adequacy or inadequacy of the existing legal framework. Findings revealed that multiple factors, including societal attitudes, cultural beliefs, support services, and the duration of the trial process, shape victims' perceptions of justice. In conclusion, the adversarial system of adjudication, which limits victims’ participation, usually fails to meet their expectations. It is recommended that to improve on the gap in the justice system, there is a need for reforms and provision of various guidelines, improved victim support services, establishment of more specialised courts for sexual offences, creation of continuous public awareness, and education for victims on what to expect as they navigate the justice system. Once victims are recognised, their voices are heard for the crime committed against them. Through this, the justice system establishes an equitable system that supports victims.